Flexible ferroelectric devices: status and applications - Jia, Xiaotong (2022)
Flexible electronic devices have been extensively studied for their advantages of distinguished portability, conformal contact characteristics, and human-friendly interfaces compared with conventional bulk Si technology. Flexible electronics can be attached to various surfaces like skin and internal organs for human–machine interaction, which has made significant advances in electronics, medicine, neuromorphic computing, etc. Owing to the innovation and maturation of the thin film preparation process, which have promoted the successful preparation of high-quality flexible ferroelectric films. Herein, the preparation of flexible ferroelectric devices and the progress of their applications in recent years are reviewed. Prevailing methods for preparing flexible ferroelectric films including the van der Waals heteroepitaxy on flexible substrate, delamination of the ferroelectric films on rigid substrate by chemical etching techniques, and direct use of novel 2D ferroelectric materials etc. are summarized. The research progress of flexible ferroelectric devices applied to memories, sensors, photovoltaic devices, and energy harvesters are also be discussed in detail. Moreover, the potential applications of flexible ferroelectric devices in the field of neuromorphic computing are studied, a new trend which contributes to the further development of brain-like chip systems. Finally, the challenges and prospects of flexible ferroelectric devices in the future advanced electronics are briefly proposed.